2018
DOI: 10.1111/emr.12294
|View full text |Cite
|
Sign up to set email alerts
|

Revegetation, restoration and reptiles in rural landscapes: Insights from long‐term monitoring programmes in the temperate eucalypt woodlands of south‐eastern Australia

Abstract: Summary Over the past decade, there has been a concerted effort to better understand the distribution and abundance of reptiles in agricultural landscapes and to specifically evaluate their response to revegetation (tree and shrub plantings) and habitat restoration in the wheat‐sheep belt of south‐eastern Australia. This article reviews the response of reptiles to revegetation and woodland management and provides ten insights and lessons that can be applied to help improve reptile conservation in temperate euc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 68 publications
0
15
0
3
Order By: Relevance
“…Intensively managed farmland may reduce cross‐habitat movements and have negative impacts on species reliant on woodland habitat. While plantings may provide habitat for some reptile species (Munro, Lindenmayer & Fischer, ; Lindenmayer et al ., ; Michael et al ., ), our results suggest plantings may not mitigate the negative effects of broader habitat loss in agricultural areas, especially for species reliant on microhabitat features associated within mature native vegetation (Cunningham et al ., ; Neilly et al ., ). Our data indicated that radio‐tracked, resident geckos did not incorporate plantings into their home ranges, and orientation and movement patterns suggest avoidance of this habitat in favour of patches.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Intensively managed farmland may reduce cross‐habitat movements and have negative impacts on species reliant on woodland habitat. While plantings may provide habitat for some reptile species (Munro, Lindenmayer & Fischer, ; Lindenmayer et al ., ; Michael et al ., ), our results suggest plantings may not mitigate the negative effects of broader habitat loss in agricultural areas, especially for species reliant on microhabitat features associated within mature native vegetation (Cunningham et al ., ; Neilly et al ., ). Our data indicated that radio‐tracked, resident geckos did not incorporate plantings into their home ranges, and orientation and movement patterns suggest avoidance of this habitat in favour of patches.…”
Section: Discussionmentioning
confidence: 71%
“…Behavioural avoidance of farmland generally by geckos, irrespective of matrix type, may be a greater barrier to animal movement than the physical structure of differing matrix types. Our results highlight the importance of remnant native vegetation, particularly with mature microhabitat features such as large trees with exfoliating bark and dead standing trees, for preserving reptile populations in modified cropping landscapes (Brown, Bennett & Potts, ; Lindenmayer et al ., ; Michael et al ., ). Our findings also highlight the likely negative consequences of habitat loss and degradation for native biota (Prevedello & Vieira, ; Bonte et al ., ; Baguette et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…If this trend continues, land managers who rely on availability of local livestock to graze conservation reserves, such as those in the study region, may be forced to make such switches. Similar transitions between different types of grazers have occurred in other grassy biomes with mixed outcomes for biodiversity (Michael et al, 2018;Schmitz & Isselstein, 2020;Sliwinski et al, 2020). Addressing the question of what ecological implications may flow from grazer regime shifts in native grasslands of Australia should be a priority for research.…”
Section: Discussionmentioning
confidence: 96%